Implementasi Kebijakan Tata Kelola Rehabilitas Hutan Mangrove di Kelurahan Oesapa Barat, Kecamatan Kelapa Lima (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study aims to analyze the implementation of mangrove rehabilitation policies after Cyclone Seroja in West Oesapa Village, Kupang City, using Merilee S. Grindle's policy implementation theory and the principles of good governance. Mangrove rehabilitation is a crucial step in the recovery of coastal ecosystems affected by disasters, but in practice it often faces various obstacles, both in terms of institutions, coordination between actors, and community participation. This study uses a descriptive qualitative approach. Data collection techniques were carried out through in-depth interviews with nine informants consisting of representatives of government agencies (DLHK, BKSDA), field supervisors, NGO administrators, RT heads, and local communities. Data analysis was carried out by referring to two main variables of Grindle's theory, namely policy content and implementation context, which were then combined with governance principles such as coordination, participation, transparency, effectiveness, and accountability. The results of the study indicate that the implementation of the mangrove rehabilitation policy in West Oesapa does not fully reflect the principles of good governance. Coordination between actors is not optimal, community participation is still passive, and post-implementation monitoring mechanisms have not been implemented. The dominance of technical implementers and minimal community involvement in planning are major obstacles to achieving program sustainability. Therefore, strengthening collaborative governance and community empowerment is needed to ensure effective and sustainable mangrove rehabilitation.